Grain Export as a Factor of Sustainable Development of Rural Territories of the Omsk Region - Novikov Y.; Baetova D. (Техника и технология пищевых производств)
In response to the current devaluation of the ruble, the Russian Government takes measures to support exporters. Thus, the most important factor of sustainable development of rural territories is their commitment to export, which explains the relevance of the present research that features the problems and top trends of grain export in the Omsk region. The theoretical part of the study develops the concept and properties of sustainable development of rural territories, its dependence on the efficiency of agricultural producers, and the situation in the Omsk region. The survey part of the paper investigates the grain export in 2015–2017: the share of the Omsk region in Russian grain export; the share of grain export in the total volume of export sales the dynamics of grain export and a review of factors of influence; a structural and dynamic analysis of various exports; assessment of wheat export structure by types and categories; a survey of channels of distribution of export grain (geography); an analysis of the logistic factors that limit export operations. The authors stress the positive influence of grain export on the uniform distribution of annual cash flows among the producers, which reduces the seasonal character of grain production. The trends can be explained by the specifics of grain crops, Russia’s foreign trade policy, and the logistic opportunities of the Omsk region. Sustainable development of the region requires a higher volume of grain export, which directly depends on the wellbeing of agricultural enterprises and farms. In general, the export potential of the Omsk region will contribute to the sustainable development of its rural territories. The research results can be used in various studies connected with grain export planning and sustainable development of rural territories.